Antioxidant Activity and Bioactive Compounds of Ethyl Acetate Fractions from Syzygium cumini Wood Stem - Alawiyah, Aika Latifah; Senania, Astri (ALKIMIA, 2021)
Syzygium cumini is one of the endemic plants in Indonesia that has the potential to be developed. The fruit was known to have potential as a diabetes drug. However, very few studies to determine the medicinal potential and identification of compounds of Syzygium cumini wood stem has never been studied before. Therefore, this study aimed to determine the antioxidant activity and content of compounds in Syzygium cumini wood stem ethyl acetate fraction. The crude ethanol extract was prepared from the wood stem powder of Syzygium cumini in ethanol using maceration. Furthermore, it was carried out by the liquid-liquid fractionation process using solvents of different polarity. Antioxidant activity of the crude extract, hexane fraction, and ethyl acetate fraction was determined by spectrophotometric methods using 1,1-diphenyl-2-picrylhydrazyl (DPPH). Analysis of bioactive compounds by using Thin Layer Chromatography (TLC). Identification of compounds functional groups was carried out to support the results of TLC analysis by using Fourier-transform infrared (FTIR). Ethyl acetate fraction showed the highest antioxidant activity (IC50 13,62 µg/mL), followed by ethanol extract (IC50 19,64 µg/mL) and hexane fraction (IC50 61,25 µg/mL). The antioxidant activity of the acetate fraction was lower than that of ascorbic acid with an IC50 value of 2,85 µg/mL. However, this fraction has very strong antioxidant activity. The TLC analysis results showed that the sample was thought to contain an alkaloid, phenolic, flavonoid, and terpenoid. The assumption on agreement with FTIR analysis which showed functional groups were C-H, O-H, N-H, C=O, and C=C aromatics as constituents of these compounds.